If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5/6x-1/3x=x-3/2
We move all terms to the left:
5/6x-1/3x-(x-3/2)=0
Domain of the equation: 6x!=0
x!=0/6
x!=0
x∈R
Domain of the equation: 3x!=0We add all the numbers together, and all the variables
x!=0/3
x!=0
x∈R
5/6x-1/3x-(+x-3/2)=0
We get rid of parentheses
5/6x-1/3x-x+3/2=0
We calculate fractions
162x^2/72x^2-x+60x/72x^2+(-24x)/72x^2=0
We add all the numbers together, and all the variables
162x^2/72x^2-1x+60x/72x^2+(-24x)/72x^2=0
We multiply all the terms by the denominator
162x^2-1x*72x^2+60x+(-24x)=0
We add all the numbers together, and all the variables
162x^2+60x-1x*72x^2+(-24x)=0
Wy multiply elements
162x^2-72x^3+60x+(-24x)=0
We get rid of parentheses
162x^2-72x^3+60x-24x=0
We do not support expression: x^3
| 3x-11=7x-4(x-11) | | X+1/8y+5/4=-3/8(y-5/6) | | 1/2=3/2k+3/2 | | 9+6s=87 | | -7-7/5k=28 | | 3(2-6x)=6 | | –2(d+7)-(3d+5)=2d+(4d-9+3d)-(d-3) | | 11=3−43x | | r/4+15=24 | | -241=-8(3r+10)+r | | x+3.75=34/3 | | 3x-8(x-6)=21 | | (X+10)+y=64 | | (5x-8)-(x+6)=18 | | 0.11x+0.04(19000-x)=1390 | | y=2(-3)^2-3(-3)-2 | | 2x^2+6x-5=85 | | -10(-8)=x/10 | | 1/5t-4+2/5t=-6-1/10t | | 7x+-2=33 | | 7(x+5)-3=4+2(x-1) | | 8.5x+1.10=2.5x+2.25 | | 4(x-3)+52=-4xA. | | s/3+-5=-2 | | 5=4.5x | | d−8−2=12d−8−2=12 | | 0.04x+0.11(19000-x)=1390 | | 75xX=250 | | 5x+48=-27 | | -250x+450=1700 | | 2(m+43)=36 | | 5-c/3=2c+2/4 |